2021
DOI: 10.31234/osf.io/c4w7p
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fatigue symptoms associated with COVID-19 in convalescent or recovered COVID-19 patients; a systematic review and meta-analysis

Abstract: BackgroundThe prevalence and prognosis of post-acute stage SARS-CoV-2 infection fatigue symptoms remain largely unknown.AimsWe performed a systematic review to evaluate the prevalence of fatigue in post-recovery from SARS-CoV-2 infection.MethodMedline, Embase, PsycINFO, CINAHL, Web of Science, Scopus, trial registries, Cochrane Central Register of Controlled Trials and Google Scholar were searched for studies on fatigue in samples that recovered from PCR diagnosed COVID-19. Meta-analyses were conducted separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
9
0
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 21 publications
4
9
0
3
Order By: Relevance
“…Our prevalence rates of dyspnea and fatigue at the different follow-up periods are similar to those reported in current literature [ 3 , 4 ]; however, we recognized that collecting fatigue as an onset symptom at hospital admission during the first wave of the pandemic was difficult because several subjects confused it with generalized viral-induced myalgias (general tiredness painful sensation). In fact, dyspnea and fever are the most bothersome COVID-19 symptoms self-reported by the patients at hospital admission.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Our prevalence rates of dyspnea and fatigue at the different follow-up periods are similar to those reported in current literature [ 3 , 4 ]; however, we recognized that collecting fatigue as an onset symptom at hospital admission during the first wave of the pandemic was difficult because several subjects confused it with generalized viral-induced myalgias (general tiredness painful sensation). In fact, dyspnea and fever are the most bothersome COVID-19 symptoms self-reported by the patients at hospital admission.…”
supporting
confidence: 88%
“…Further, according to a meta-analysis published in the Eur J Internal Medicine , fatigue and dyspnea are also the most prevalent post-COVID symptoms [2] . Another meta-analysis specifically evaluating post-COVID fatigue reported a prevalence rate of 42% the first six months after the infection [3] . The presence of post-COVID fatigue is associated with worse quality of life [4] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence rates of post-COVID fatigue and dyspnea observed in our study agree with current meta-analyses on the topic [5, 6] suggesting that our sample is representative of long-COVID patients. Potential pathophysiologic mechanisms proposed for explaining post-COVID fatigue and dyspnea include a systemic immune response with prolonged inflammation and atypical response of the mast cells, persistent viral replication/toxicity, hypercoagulability, and the presence of residual lung injury [10-12].…”
Section: Discussionsupporting
confidence: 91%
“…Different meta-analyses had reported that the prevalence of post-COVID symptoms ranges from 35% to 60%, depending on the symptom and the follow-up [3, 4]. Fatigue and dyspnea seem to be the most prevalent post-COVID symptoms reaching up to 50% of COVID-19 survivors [5, 6]. The association between post-COVID symptoms and laboratory biomarkers is controversial.…”
Section: Introductionmentioning
confidence: 99%